2020
DOI: 10.15430/jcp.2020.25.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking on Human Natural Killer Cell Activity: A Large Cohort Study

Abstract: Some studies have reported a decrease in the natural killer (NK) cell activity in smokers. However, large-scale data on the relationship between NK cell activity and smoking are unavailable. A cross-sectional study was performed on 12,249 asymptomatic examinees who underwent an NK cell activity test, between January 2016 and May 2017. The test quantitated the amount of interferon-γ secreted into the plasma by NK cells, using a patented stimulatory cytokine. The mean age of the study population was 39.1 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This method is used in the ongoing immune cell therapy project of the oncology department of our hospital to assist in the assessment of the patient's immune function status, and to provide a reference for clinical treatment as a basis for follow-up (research results have not yet been published). However, due to many personal life reasons or consumption of drugs, etc., it will affect the individual's NK cell activity products, which will bias the final test results, such as stress and sleep disorders [35] [36], take steroid drugs [35] [36] [37] [38], proton pump inhibitors [39], long-term smoking [40], drinking [41] and foods rich in zinc and selenium [42] [43], etc., will temporarily decrease or increase the value of NK cell activity high. Therefore, the clinical application of this method needs to be further verified, and the influence of more exclusionary factors needs to be considered.…”
Section: Nk Vue Cytokine Release Methodsmentioning
confidence: 99%
“…This method is used in the ongoing immune cell therapy project of the oncology department of our hospital to assist in the assessment of the patient's immune function status, and to provide a reference for clinical treatment as a basis for follow-up (research results have not yet been published). However, due to many personal life reasons or consumption of drugs, etc., it will affect the individual's NK cell activity products, which will bias the final test results, such as stress and sleep disorders [35] [36], take steroid drugs [35] [36] [37] [38], proton pump inhibitors [39], long-term smoking [40], drinking [41] and foods rich in zinc and selenium [42] [43], etc., will temporarily decrease or increase the value of NK cell activity high. Therefore, the clinical application of this method needs to be further verified, and the influence of more exclusionary factors needs to be considered.…”
Section: Nk Vue Cytokine Release Methodsmentioning
confidence: 99%
“…In a murine lung metastasis model, cigarette smoking impaired NK-cell-dependent tumor immunosurveillance, and the resulting altered immunity was associated with an increased tumor burden [ 84 ]. Studies in humans have shown that NK cell activity is reduced in smokers [ 45 , 46 , 47 , 48 ]. Recently, a large cross-sectional study has shown an inverse correlation between NK cell activity and the number cigarettes smoked daily, and the total number of cigarettes smoked [ 48 ].…”
Section: Lifestyles and Nk Cellsmentioning
confidence: 99%
“…Studies in humans have shown that NK cell activity is reduced in smokers [ 45 , 46 , 47 , 48 ]. Recently, a large cross-sectional study has shown an inverse correlation between NK cell activity and the number cigarettes smoked daily, and the total number of cigarettes smoked [ 48 ]. Cigarette smoke reduces the cytolytic granules of perforin, granzymes, and granulysin on NK cells [ 49 ].…”
Section: Lifestyles and Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, dysregulated inflammatory response may be crucial [ 17 , 18 ]. In smokers, lower circulating NK cells level may accelerate cancer progression, which in turn can lead to an exacerbation of side effects of cancer treatment [ 19 ].…”
Section: General Information About Lung Cancer: Incidence Risk Famentioning
confidence: 99%